The Malay Muslim cancer patients’ perspectives on Islamic healing cancer treatment - Suhami, Norhasmilia (2014)
Cancer patients want to be treated as a whole person including their physical, emotional and spiritual dimensions. For Muslim, they tend to use healing methods that are related to their Islamic tenets. Therefore, there is a growing number of Malay Muslim cancer patients seeking Islamic healing, but little empirical work exists on the use of Islamic healing. The purpose of this study is to understand: (1) why Malay Muslim cancer patients seek Islamic healing, (2) Islamic healing treatment, and (3) Islamic healing benefit and role in cancer treatment. A qualitative study was conducted using in-depth interviews with 15 Malay Muslim women cancer patients that sought both conventional system and Islamic healing from 4 different regions in Peninsular Malaysia. The participants were selected from purposive sampling and snowball tehnique. The following are the reasons cancer patients seek Islamic healing; (1) recommendation from family, friends and doctors, (2) belief in Islamic healing and (3) ineffectiveness or dissatisfaction with the conventional treatment. Islamic healing treatment can be categorized into two forms; (1) recitation of Quranic verses as a main method with du‘a and Sunnah (voluntary) salat and (2) a combination of herbs with recitation of Quranic verses, du‘a and healing water. Benefits and role of Islamic healing (1) provide physical and spiritual benefits and (2) as a complementary treatment to conventional medicine. The evidences suggest that Islamic healing will continue to be as a popular healing choice among Malay Muslims. The use of Islamic healing as a complementary treatment has its own potential as it is a holistic and natural healing. This finding is the first formal research of this type of study and needs to be considered by policy makers in providing a better health care system for the country.